URBAN PLANNING AND RECONSTRUCTION REGIONAL ENGINEERING TRAINING - A.M. Хaydarov; N.S.Tursunov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The issues of application of several methods of vertical planning in solving problems related to land works arising in the process of reconstruction and reconstruction of cities are presented.